Hypochlorous Acid for Wound Healing in Diabetic Rats: Effect on MMP-9 and Histology - Irawan DM; Lesmana R; Sahiratmadja E (Dove Medical Press, 2024)
Dita Mutiara Irawan,1 Ronny Lesmana,2- 4 Edhyana Sahiratmadja4 1Graduate School of Master Program in Anti Aging and Aesthetic Medicine, Faculty of Medicine, Universitas Padjadjaran, Jatinangor, 45363, Indonesia; 2Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, 45363, Indonesia; 3Division of Biological Activity, Central Laboratory, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 4Department of Biomedical Science, Faculty of Medicine, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Dita Mutiara Irawan, Email dita22007@mail.unpad.ac.idBackground: People who suffered type 2 diabetes have impaired healing of wounds due to the large number of circulating inflammatory cells resulting from high blood sugar levels. The wound healing process involves various complex processes including the degradation of extracellular matrix, a process characterized by an increase in matrix metalloproteinase-9 (MMP-9). Conventional management of diabetic wounds usually involves systemic blood sugar control and topical antimicrobial treatment, including hydrogen peroxide and povidone-iodine, which are known to be cytotoxic to the cells involved in the wound healing cascade. Finding a safe, non-toxic, and effecting wound cleansing still poses a challenge, and hypochlorous acid (HOCl) could act as a potential candidate.Purpose: Unveiling an HOCl ion as an agent for diabetic wound management and MMP-9 as a marker for delayed diabetic wound healing.Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Flow Diagram is used to find and select related, eligible literatures for the review. The authors used several databases such as Pro Quest, Scopus, Springer link and Science Direct. In addition, and to expand the data, the database on Google Scholar was also opened. Then, the compiled data are analyzed to form results and discussions to the research question.Results: Five eligible articles passed the inclusion criteria and reviewed for data synthesis. From 5 pieces of literature, it was found that the use of HOCl ions can be a good choice of topical agent in the management of diabetic wounds and decrease the activity of MMP-9, which act as a marker for delayed healing of diabetic wounds.Conclusion: Topical agent, in this case HOCl ion, shows good results and can be used as an option in the management of diabetic wounds and MMP-9 can be used as a predictive marker in the management of diabetic wounds.Keywords: diabetic wound, HOCl ion, hypochlorite acid, MMP-9, wound healing